The Bamboo Business in Tasikmalaya, Indonesia, During the COVID-19 Pandemic - Widiyanto , Ary; Suhartono, Suhartono; Utomo , Marcellinus; Ruhimat, Idin Saepudin; Widyaningsih, Tri Sulistyati; Palmolina, Maria; Fauziyah, Eva; Sanudin, Sanudin (Forestry Faculty, Universitas Hasanuddin, 2021)
Globally, various sectors were adversely affected by the emergence of the COVID-19 pandemic. Therefore, this study aims to determine the economic condition of bamboo craftsmen in Mandalagiri Village, Leuwisari District, Tasikmalaya Regency, West Java Province, Indonesia. This is an in-depth research with data obtained by interviewing 35 bamboo craftsmen with various products and production scales. The results showed that craftsmen were not economically affected by the pandemic rather by the central government-stipulated regulation on social distancing, which led to their inability to transport their product from Tasikmalaya to Jakarta and other regions. However, since the government lifted the ban, their income has increased by an average of 2%. The result further showed that the main factor that keeps craftsmen from being negatively affected by the pandemic is the increasing online market demand supported by the availability of raw materials and the ability to adapt to various new model products. Other factors linked to the national market and products answer the demand of the modern market in the cities. Meanwhile, the main factors that positively affect the craftsmen's income are age and marital status.